1996
DOI: 10.1021/ma951132t
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Studies of Lightly Sulfonated Polystyrene Using 23Na NMR:  Effects of Polydispersity in Molecular Weight

Abstract: Ion content and molecular weight have been shown to affect the 23Na NMR spectra of monodisperse sodium-neutralized sulfonated polystyrene ionomers (MNaSPS). A new NMR peak at −2.7 ppm appears at ionization levels above 1.2% and molecular weights of a least 35 000; this peak is not present in polydisperse NaSPS. The fraction of NMR intensity due to this peak is relatively constant above M n ∼ 100 000. It is proposed that this peak is due to a distorted version of an isolated site. Along with the new −2.7 ppm pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…For the ionomer that was treated with TEOS using MeCl 2 , the peak is shifted to −7.9 ppm which indicates, based on prior similar studies,28–31 that the Na + ions, on the average, are less associated with each other than they would be in the unfilled control. Perhaps this peak shift might be accounted for by silicate structures that, in the course of their growth, have intruded between some of the associations of PET–SO 3 Na + ion pairs so as to weaken interpair interactions.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…For the ionomer that was treated with TEOS using MeCl 2 , the peak is shifted to −7.9 ppm which indicates, based on prior similar studies,28–31 that the Na + ions, on the average, are less associated with each other than they would be in the unfilled control. Perhaps this peak shift might be accounted for by silicate structures that, in the course of their growth, have intruded between some of the associations of PET–SO 3 Na + ion pairs so as to weaken interpair interactions.…”
Section: Resultsmentioning
confidence: 83%
“…These field gradients can be especially due to the strong electric fields posed by other Na + ions or to polymer‐affixed anions, such as—SO 3 groups, in the vicinity. It has been established that as peaks shift to less negative values, the interactions with Na + ions become weaker 24–32. This concept can be put to use in determining whether Na + ions are isolated or exist in aggregates, although the absolute size of these aggregates cannot be derived from this method.…”
Section: Resultsmentioning
confidence: 99%
“…23 Na NMR experiments can be used to determine quantitatively the amount of isolated ions in sodium-neutralized ionomers; these experiments are critically important since they represent the only quantitative example where the fraction of isolated ions was determined for nontransition-metal neutralized materials. In a series of papers [29,[50][51][52], Cooper and coworkers used NMR to study NaSPS in great detail. The authors found that in fully neutralized samples at $2 mol% sulfonation level, the sodium atoms were both isolated and aggregated; while at $4 mol% sulfonation level, all sodium atoms were aggregated.…”
Section: Ionomer Synthesismentioning
confidence: 99%
“…The sodium nuclei existing in lone ion pairs yield a sharp peak centered around 7 ppm, while the sodium nuclei in the ionic aggregates (i.e. doublets, triplets,., multiplets) yield a broad peak centered in the range from K 8 to K12 ppm [22,[26][27][28][29]. Fig.…”
Section: Solid-state 23 Na Nmrmentioning
confidence: 96%
“…O'Connell et al [26][27][28][29] have shown that sodium ions in dry, lightly sulfonated polystyrene ionomers may exist in two distinctly different environments: (1) isolated sodium nuclei in lone sodium-sulfonate ion pairs and (2) sodium nuclei in close proximity to other sodium nuclei (i.e. in ionic aggregates).…”
Section: Solid-state 23 Na Nmrmentioning
confidence: 99%